PENANGGULANGAN KEMISKINAN DALAM PENCAPAIAN MILLENNIUM DEVELOPMENT GOALS (MDGs) - Karmanis - Tri Lestari H (Serat Acitya, 2015)
In the 1970s,Indonesiais one of thepoorest countries inAsia. In 1976, 54million people in Indonesia(40% of the population) belong to the categoryof poor. In1980-1990anperiodis a period ofhigh economic growth. High economicgrowthis closely linkedwithpoverty reductiondrasticallywhere the numberof poor peoplefell by almost50% from40millionto 22million peoplein 1981s/d1996.In the year2010 the numberof poor peopleamounted to31.02 million people, or about 13:33% andthe poverty ratein March2009 amounted to32.53million, or about 14:15% (BPS). LastBPS dataperSeptember 2013shows that there are28.59millionor11.66% ofthe totalpopulationinIndonesia.PovertyinIndonesia hasdecreasedsignificantlysincethe reformera. Acceleration ofpoverty reductionprogramsinIndonesiais donewithgoodsynergywork programsatnational and local levels. Poverty reduction programscurrently dividedinseveralclusters: Cluster(1) Direct AidSociety(BLM). Thisclusterincludes theSchool Operational Assistance(BOS), Community Health Insurance(Assurance), Ricefor the Poor(Raskin), Family Hope Program(PKH). Cluster1goalistoreducepovertyandimprove thequality ofhuman resources, especiallythe poor.Cluster (2) is the national community empowerment Program (PNPM) independently. The purpose of PNPM Mandiri is to increase prosperity and employment opportunities of the poor independently. Cluster (3) people's business credit (KUR) is a people's business credit is given to the poor without collateral to the community a certain amount. Purpose to provide and strengthening economic access for businessmen of small and micro-scale. An important aspect in strengthening is giving them freely to access of the poor to be able to try and improve the quality of life.In 2011 the Government carry out a Cluster of clusters of four. This Cluster includes: (1) the provision of the House very cheap, (2) a cheap public transport Vehicles, (3) clean water to the people, (4) enhancement of Life for fishermen, (5) improvement of Urban Edge Community Life. The 4 Cluster in the framework of poverty reduction and the achievement of the Millennium Development Goals (the Millennium Development Goals (MDGs), so the expected goal of the Millennium Development Goals (the Millennium Development Goals (MDGs) by 2015 is reached. As it known that the millennium development goals (the Millennium Development Goals (MDGs) is an attempt to meet the basic needs of the rights of man through a joint commitment between the 189 UN Member States to implement the 8 (eight) Millennium development goals, namely (1) tackling poverty and hunger, (2) achieve primary education for all, (3) encourage gender equality and the empowerment of women, (4) reduce child mortality, (5) improve maternal health, (6) fight against spread of HIVAIDS, malaria and other contagious diseases, (7) Living and Sustainability (8) global partnership in development. Eight of these targets as measurable goals for a single package of development and poverty reduction.In September 2000, the United Nations Millennium Summit, where world leaders agreed on eight development goals that are specific and measurable global called the Millennium Development Goals (MDGs). The first seven goals focus on eradication of extreme poverty and hunger, achieve universal primary education, promoting gender equality and empowering women, reducing child mortality; In September 2000, the United Nations improve maternal health, combat HIV-AIDS, malaria and other diseases, and ensuring environmental sustainability. Whereas the eighth goal calls for the establishment of a global partnership for development, with targets for aid, trade and debt relief.However approach the year 2015, global world will experience the transformation of the global development of the Millennium Development Goals (MDGs) into Sustainable Development Goals (SDGs). The shifting of the MDGs to the SDGs doesn't mean the goal contained in the MDGs fail is reached. Quite the contrary, many world records that reveal the success in various countries, there is a remarkable improvement experienced by the poor countries in the ranking of HDI (human development index) the lowest. In the last 40 years, the State- countries that are in the lowest rank of 25 percent experienced improved HDI to 82. The IMF report in the 2013 Global Monitoring Report also explain the positive trend in the achievement of the MDGs. reduction of half of the world's poor population, reduction of half of the population without access to clean water, the Elimination of gender inequality in primary education in 2015, and the improvement of life in a hundred million slums by 2020 was reached more quickly, i.e. in 2010. ADB, a number of countries in Asia also experienced progress in achieving the millennium development goals. The number of poor population has decreased significantly in Malaysia, Viet Nam and China. In Thailand and Malaysia, long-term policies to overcome poverty coupled with their concern for the environment has made the countries that are in the lowest rank of 25 percent experienced improved HDI to 82. The IMF report, these countries are on a sustainable growth path. But not so the case with Indonesia, a country with a diversity of biodiversity in forests is raining but the risorsis contained therein are not managed sustainably and fairly.Programme of the Millennium Development Goals (MDGs) will be forwarded to Suistanable Development Goals (SDGs). The MDGs will expire in 2015, but until now there has been no final draft which will forward the MDGs program. to that end, scientists and many quarters trying to deepen the concept of SDGs as successor to the MDGs. Keywords: Millennium Development Goals (MDGs), Sustainable Development Goals (SDGs), primary education, maternal health, clean water.